Estimating the Public Health Burden Associated With Adverse Pregnancy Outcomes Resulting From Syphilis Infection Across 43 Countries in Sub-Saharan Africa. Issue 7 (July 2015) - Kuznik, Andreas; Habib, Abdulrazaq G.; Manabe, Yukari C.; Lamorde, Mohammed
Abstract : Background: Untreated syphilis in pregnancy is associated with adverse clinical outcomes to the infant. The study aimed to estimate the public health burden resulting from adverse pregnancy outcomes due to syphilis infection among pregnant women not screened for syphilis in 43 countries in sub-Saharan Africa. Methods: Estimated country-specific incidence of syphilis was generated from annual number of live births, the proportion of women with at least 1 antenatal care (ANC) visit, the syphilis prevalence rate, and the proportion of women screened for syphilis during ANC. Adverse pregnancy outcome data (stillbirth, neonatal death, low birth weight, and congenital syphilis) were obtained from published sources. Disability-adjusted life-year (DALY) estimates were calculated using undiscounted local life expectancy, the neonatal standard loss function, and relevant disability weights. The model assessed the potential impact of raising ANC coverage to at least 95% and syphilis screening to at least 95% (World Health Organization targets). Results: For all 43 sub-Saharan Africa countries, the estimated incidence of adverse pregnancy outcomes was 205, 901 (95% confidence interval [CI], 113, 256–383, 051) per year, including stillbirth (88, 376 [95% CI, 60, 854–121, 713]), neonatal death (34, 959 [95% CI, 23, 330–50, 076]), low birth weight (22, 483 [95% CI, 0–98, 847]), and congenital syphilis (60, 084 [95% CI, 29, 073–112, 414]), resulting in approximately 12.5 million DALYs. Countries with the greatest burden are (in DALYs, millions) Democratic Republic of the Congo (1.809), Nigeria (1.598), Ethiopia (1.466), and Tanzania (0.961). Attaining World Health Organization targets could reduce the burden by 8.5 million DALYs. Conclusions: Substantial infant mortality and morbidity results from maternal syphilis infection concentrated in countries with low access to ANC or low rates of syphilis screening. Abstract : Findings from a model to calculate disease burden suggest that substantial infant morbidity and mortality arises from maternal syphilis infection in sub-Saharan Africa.